2017
DOI: 10.1093/infdis/jix466
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Central Nervous System Disease in Trypanosoma brucei rhodesiense Infection

Abstract: 1H nuclear magnetic resonance metabolic profiling of cerebrospinal fluid demonstrated that biochemical markers were associate with presentation of neurological symptoms in African trypanosomiasis, rather than disease stage. Thus, disease staging using standard diagnostic methods may not accurately mirror the invasion of the brain by parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Even so—and similarly to proteomics—the most significant changes in metabolite abundances between HAT stages were observed in the CSF, indicating that finding a blood (or urine) staging tool with the appropriate specificity and sensitivity remains a difficult task. Different results have very recently been published on T. b. rhodesiense CSF samples using 1 H NMR spectroscopy . No CSF metabolic marker was able to differentiate between stages, however, altered levels of specific metabolic features (including 3‐hydroxybutyrate, alanine, mannose, and urea) were reported to be indicative of the presence of neurological signs, independently from the disease stage, and to correlate with neuro‐inflammation.…”
Section: Omics and Hat Biomarkersmentioning
confidence: 91%
“…Even so—and similarly to proteomics—the most significant changes in metabolite abundances between HAT stages were observed in the CSF, indicating that finding a blood (or urine) staging tool with the appropriate specificity and sensitivity remains a difficult task. Different results have very recently been published on T. b. rhodesiense CSF samples using 1 H NMR spectroscopy . No CSF metabolic marker was able to differentiate between stages, however, altered levels of specific metabolic features (including 3‐hydroxybutyrate, alanine, mannose, and urea) were reported to be indicative of the presence of neurological signs, independently from the disease stage, and to correlate with neuro‐inflammation.…”
Section: Omics and Hat Biomarkersmentioning
confidence: 91%
“…In murine models, trypanosome infection is associated with global host metabolic disturbances, including in the bloodstream, but also in other anatomical locations such as the gut and brain [ 170 , 181 , 182 ]. These changes are the result of both host and parasite metabolism.…”
Section: Parasite Metabolism and Virulencementioning
confidence: 99%
“…Here we have applied these light-sheets for rapid high-resolution mesoscale imaging and quantification of neuroinflammation during T. brucei infection using an experimental murine model of infection that faithfully recapitulates the severe neuroinflammatory state observed in patients infected with T. b. rhodesiense (Rodgers et al, 2015(Rodgers et al, , 2019aLamour et al, 2017) observed a significant increase in the labelling intensity of the protein glia fibrillary acidic protein (GFAP) (Yang and Wang, 2015), used here as a proxy for astrocyte reactivity and inflammation, around the circumventricular organs (CVOs), coinciding with the proposed sites of entry of the parasites into the CNS (Bentivoglio et al, 2018). Concomitantly, GFAP positive cells (typically astrocytes and ependymocytes) located in the vicinity of the ventricular structures display a greater number of cytoplasmatic processes when compared to either parenchymal astrocytes in the infected brain, or those found in naïve controls.…”
Section: Introductionmentioning
confidence: 99%